Informatics Technology-Based Learning in Barunawati Kindergarten, Kupang City - Putri Desi Adryanti Subu Taopan (International Research and Development for Human Beings (IRDH), 2026)
Along with the rapid development of technology, the world of education is required to adapt, including in early childhood education. This study aims to describe the application of information technology-based learning at Barunawati Kindergarten, Kupang City. This study uses a qualitative approach with data collection techniques through observation, interviews, and documentation. The data obtained are analyzed and described qualitatively. The results show that Barunawati Kindergarten, Kupang City has integrated information technology in digital learning activities. The application of information technology-based learning is able to increase students' interest, activeness, and understanding of the learning material. In addition, contextual and varied learning helps students gain meaningful and enjoyable learning experiences. The success of this learning implementation is supported by responsive school management, teacher competence, and parental support. Thus, information technology-based learning at Barunawati Kindergarten, Kupang City can be an example of the application of learning innovation in early childhood education.